Association between caregiver opposition to topical fluoride and COVID-19 vaccines. Issue 5 (27th January 2023) - Saini, Sapna J.; Carle, Adam C.; Forsyth, Anna R.; Chi, Donald L.
Highlights: Caregivers are hesitant about preventive care for their children. Topical fluoride opposition was associated with opposition to COVID-19 vaccines. Education level and political views were associated with opposition to the vaccine. Identifying reasons for caregiver hesitancy may help reduce some childhood diseases. Abstract: Purpose: Caregivers who oppose topical fluoride in dental settings may be opposed to other preventive health treatments, including COVID-19 vaccines. The study objective was to examine the association between caregiver opposition to topical fluoride and COVID-19 vaccines. Methods: The study took place at the University of Washington in Seattle, WA. English-speaking caregivers of children aged < 18 years were eligible to participate. An 85-item REDCap survey was administered from February to September 2021. The predictor variable was topical fluoride opposition (no/yes). The outcome was COVID-19 vaccine opposition (no/yes). The models included the following covariates: child and caregiver age; caregiver race and ethnicity, education level, dental insurance type, parenting style, political ideology, and religiosity; and household income. Logistic regression models generated odds ratios (OR) and 95 % confidence intervals (α = 0.05). Results: Six-hundred-fifty-one caregivers participated, and 403 caregivers with complete data were included in the final regression model. Mean child age was 8.5 years (SD 4.2), mean caregiver age was 42.1 years (SD 9.1), 53.0 % of caregivers were female, 57.3 % self-reported as white, and 65.5 % were insured by Medicaid. There was a significant positive association between topical fluoride and COVID-19 vaccine opposition (OR = 3.13; 95 % CI: 1.87, 5.25; p  < 0.001). Other factors associated with COVID-19 vaccine opposition included conservative political views (OR = 2.77; 95 % CI: 1.26, 6.08; p  < 0.011) and lower education (OR = 3.47; 95 % CI: 1.44, 8.38; p  < 0.006). Conclusions: Caregivers opposed to topical fluoride in dental settings were significantly more likely to oppose COVID-19 vaccines for their child. Future research should identify ways to address both topical fluoride and vaccine opposition to prevent diseases in children.